Micro/Nano-Chip Electrokinetics - Xiangchun Xuan (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Micro/nanofluidic chips have found increasing applications in the analysis of chemical and biological samples over the past two decades. Electrokinetics has become the method of choice in these micro/nano-chips for transporting, manipulating and sensing ions, (bio)molecules, fluids and (bio)particles, etc., due to the high maneuverability, scalability, sensitivity, and integrability. The involved phenomena, which cover electroosmosis, electrophoresis, dielectrophoresis, electrohydrodynamics, electrothermal flow, diffusioosmosis, diffusiophoresis, streaming potential, current, etc., arise from either the inherent or the induced surface charge on the solid-liquid interface under DC and/or AC electric fields. To review the state-of-the-art of micro/nanochip electrokinetics, we welcome, in this Special Issue of Micromachines, all original research or review articles on the fundamentals and applications of the variety of electrokinetic phenomena in both microfluidic and nanofluidic devices.